Kehidupan Sosial Ekonomi Antar Etnis Minangkabau dan Etnis Batak di Pasar Pagi Sebangsa Kota Duri (1990-2023) - Ikhsan, Maulana; Asri, Zul (Jurusan Sejarah FIS UNP, 2025)
This research focuses on socio-economic life between the Minangkabau and Batak ethnic groups at the Sebanga Morning Market, Duri City, in the period 1990-2023. In the area around the Sebanga Morning Market, there are various ethnicities, with the Batak and Minangkabau ethnic groups dominating. This causes competition and rivalry between the two ethnic groups to be superior, which often leads to conflict. The focus of this research is to analyze the social and economic life of the two ethnic groups at Pasar Pagi Sebanga, with the aim of describing the socio-economic conditions before and after the conflict between the Minangkabau and Batak ethnic groups. This research uses historical research methods to show that before 1990, competition between the Minangkabau and Batak ethnic groups at the Sebanga Morning Market had emerged, especially in economic fields such as trade and transportation. In 1990, a conflict occurred which was triggered by violations of Minang community norms by Batak youth. The conflict was finally suppressed by the authorities. After the conflict, socio-economic interactions between the two ethnic groups worsened, with the Minangkabau and Batak ethnic groups reluctant to interact with each other. However, over time, their relationship slowly improved, bringing a positive impact to socio-economic life in the region.